Alcune riflessioni sul mutamento linguistico basate sul dialetto del Torre - Spinozzi Monai, Liliana (Annales. Series historia et sociologia, 2008)
Of the three varieties of Slovene spoken in the so-called Venetic or Friulian Slovenia, the one of the upper Torre valley (Val Torre) turns out to be the most interesting for the study of contact-induced linguistic change as it shows - more clearly than the other two - signs of Romance influence, especially Friulian, due to an age-old interaction between these two systems. The analysis of some particularly revealing facts about the consequences deriving from the contiguity between Romanic and Slavic languages will be based on transcriptions carried out in the field more than a century ago by Jan Baudouin de Courtenay, who included them in his Glossario del dialetto del Torre (Glossary of the Val Torre Dialect)
Keywords: Baudouin de Courtenay, Jan; dialektologija; jeziki v stiku; jezikovne spremembe; slovenska narečja; slovenščina; Terska dolina